Survival advantage in patients with human papillomavirus‐driven oropharyngeal cancer and variation by demographic characteristics and serologic response: Findings from Head and Neck 5000. Issue 14 (15th March 2021) - Whitmarsh, Alex; Pring, Miranda; Thomas, Steve J.; Waylen, Andrea; Ness, Andy R.; Dudding, Tom; Pawlita, Michael; Brenner, Nicole; Waterboer, Tim; Schroeder, Lea
Abstract : BACKGROUND: Patients with human papillomavirus (HPV)‐driven oropharyngeal cancer (OPC) experience better survival than those with HPV‐negative OPC. It is unclear whether this benefit varies by demographic characteristics and serologic response. METHODS: Records from 1411 patients with OPC who had HPV serology data were analyzed. HPV status was based on HPV type 16 (HPV16) E6 serology. Participants were followed for a median of 5.9 years, and Cox proportional hazards models were used to estimate hazard ratios (HRs). The association between HPV status and overall survival was analyzed by age group, sex, smoking status, tumor site, HPV antibody levels, and HPV antibody pattern. Models were adjusted for age, sex, smoking status, and comorbidity. RESULTS: For the overall association between HPV status and survival, the fully adjusted HR was 0.43 (95% CI, 0.33‐0.56). The HR was 0.19 (95% CI, 0.10‐0.35) for participants aged ≤54 years, 0.38 (95% CI, 0.25‐0.56) for those aged 55 to 64 years, and 0.73 (95% CI, 0.47‐1.13) for those aged ≥65 years ( P for interaction = .023). There was no clear evidence for an interaction by sex, smoking status, or tumor site. Survival did not differ according to E6 antibody levels in those who were seropositive. All seropositivity patterns were associated with increased survival compared with a pattern of seronegativity for all antibodies. Patients who are positive for E1, E2, E6, and E7 may experience better survival. CONCLUSIONS: HPV status confers a survival advantage across all groups. This survival advantage is more marked for younger patients. The HPV antibody pattern, but not the antibody level, may also affect survival. Abstract : This study investigates whether the survival advantage of patients who have human papillomavirus‐driven oropharyngeal cancer vary by demographic and serologic characteristics. The survival advantage is more marked for younger individuals and for those who are seropositive for all 4 antibodies investigated (E1, E2, E6, and E7).